Tebang pilih tanam jalur : pemodelan pertumbuhan tanaman meranti pada jalur tanam - . Wahyudi; Andry Indrawan; Irdika Mansur; Prijanto Pamoengkas (Institut Pertanian Bogor, 2010)
Selective Cutting and Line Planting (SCLP) silvicultural system can be applied in the logged over forest and low potential forest to improve their productivity . The research was aimed to create the growth modelling of Shorea plantations in the line planting system. The research was conducted at research plots of SCLP in logged over forest of PT Gunung Meranti, Central Kalimantan Province. The research plots were divided into three plots of Shorea Jeprosula plantation that planted in 1994 as plot 1, year 1999 as plot 2 and year 2008 in which consisted of 200 samples of trees, respectively. Data of Shorea Jeprosula growth were evaluated by Stella 9.0.2 and SPSS 13, and predicted using table of volume, exponential and polynomial equations. The research result showed that exponential equation was y= 1,0269.e0,012x(R2= 96,02%) and estimated cutting cycle at 37 year old, average polynomial equation was y=0,0297x2+ 0,8208x + 0,3728 (R2= 86,89%) and estimated cutting cycle at 30 year old and group polynomial equations (R2> 95%) estimated cutting cycle at 32 years old. The best model was group polynomial equations that represented exponential equation and average polynomial equation in the yield of volume.